PERANCANGAN APLIKASI KONVERSI KALENDER MASEHI KE KALENDER ROMAWI (FASTI ROMANI) MENGGUNAKAN METODE FUZZY STRING MATCHING BERBASIS ANDROID - Istiyono (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Smartphones are no longer just a means of communication, but a tool for banking, shopping and education. You can also use your smartphone for currency, temperature, calendar, and other conversions. In this final project, the author converts the Gregorian calendar to the Roman calendar. The Roman calendar is sometimes called the Gregorian calendar or an earlier version of the Gregorian calendar. What makes it stand out, though, is the reference to the calendar. Where the Gregorian calendar uses prime numbers to indicate dates, the Roman calendar uses word-level numbers. The Gregorian to Roman (Fasti Romani) conversion in this study uses a fuzzy string matching method and uses a brute force algorithm implemented in an Android based application. This Android-based application can be used without an Internet network connection, so you can use it anytime, anywhere. The purpose of this study is to help Latin learners who are struggling to convert from the Gregorian calendar to the Roman calendar due to very few Latin textbooks in Indonesia.